Pemanfaatan Aplikasi Kamus Melayu Jambi Dialek Jambi Seberang: Menguatkan Kearifan Lokal Dalam Pembelajaran Budaya Di Sekolah Dasar - Saputra, Edi; Khaira, Ulfa; Razi A, Muhammad; Suratno, Tri; Priyanto, Priyanto (Universitas Negeri Gorontalo, 2024)
The Jambi Seberang Malay dialect is on the verge of extinction due to a decrease in its usage, especially among the younger generation. Contributing factors to this decline include globalization, changing demographics, and a lack of resources. To counteract this, the Jambi Provincial Language Office has developed an e-book dictionary, but its usability is limited. To improve accessibility, a research team from Jambi University developed a mobile app. This community service project aimed to promote the dialect by integrating it into elementary school curricula, using the mobile app as a fun and easy-to-use learning tool. A workshop held at SDN 03 Olak Kemang on September 30, 2024, resulted in increased understanding of the dialect among both teachers and students.